Peran Koperasi dan Investasi Terhadap Pertumbuhan Ekonomi di DKI Jakarta dan Jawa Barat serta Dampaknya pada Pengangguran - Perkasa Alam, Bambang; Arifin Masri , Zainal; Yuliasari, Indah; Barkah, Januar (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to examine the role of cooperatives and investments in economic development and their impact on unemployment in DK Jakarta and West Java. Data was obtained from the Central Bureau of Statistics (BPS) from 2001 to 2022. The data analysis technique used was multiple linear regression. The results showed that the number of cooperatives, the number of cooperative members, and own capital have the following relationship: Y=12.70-0.00X1-2.58E-07X2+5.41E-09X3-9.53E-10X4-1.27E09X5-5.61E06X6. This equation implies that if the number of cooperatives, the number of cooperative members, own capital, business volume, remaining business results, and investment are in a certain condition or remain unchanged (or the change is zero), economic growth will be 12.70%. The equation Z=8.06+0.06Y implies that if economic growth is in a certain condition or remains unchanged (or the change is zero), unemployment will be 8.06%. The contribution of the number of cooperatives, the number of cooperative members, own capital, business volume, remaining business results, and investment to economic growth is only 12.8%. Meanwhile, the contribution of economic growth to unemployment is only 3%.